Doing qualitative research for beginners: from theory to practice - Sheikh Ahmad, Ismail (Partridge Publishing, 2017)
Qualitative research methods have gained popularity inside and outside the academic world. Researchers have shown growing interest in understanding an issue through qualitative, and not just quantitative, lenses.